Umbilical and middle cerebral arteries Doppler velocimetry in early and late onset pre-eclampsia - Sulaiman, Bilal; Isah, Aliyu Y.; Abdullahi, Habiba I.; Adewole, Nathaniel; Opadiran, Oluwatunmobi R.; Suleiman, Usman; Ibrahim, Rukayya; Ekele, Bisallah A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Pre-eclampsia (PE) is a multisytemic disorder originating from the placenta with a high prevalence in sub-Saharan Africa. Early (<34 weeks) and late (>34 weeks) – onset PE have different maternal and perinatal outcomes with overlapping clinical features. Differences in Doppler velocimetry pattern in these subgroups appears unsettled. Methods: In a prospective cohort study, 110 pregnant women with singleton pregnancy diagnosed with PE were recruited and had umbilical and middle cerebral arteries (MCA) Doppler velocimetry done. The pregnancies were followed up to delivery and outcome recorded and analysed using Microsoft excel 2013. Student t-test and Chi-squared test were used for continuous and categorical variables respectively. Level of significance was set at less than 0.05. Results: There were 53 (49.1%) women with early – onset preeclampsia and 55 (50.9%) with late-onset PE. The mean age of women was 30.30±5.2 years. The mean umbilical artery, middle cerebral artery pulsatility indices (PI) and cerebroplacental ratio (CPR) were 1.3±0.5, 1.1±0.5 and 1.1±1.2 respectively. There was statistical significant difference between the umbilical artery PI (p˂0.001), middle cerebral artery PI (p˂0.05) and CPR (p˂0.001) between early onset and late onset preeclamptic women. The resistance index and systolic diastolic ratio of both the umbilical and middle cerebral arteries were similar between the two groups (p>0.05). Conclusions: This study showed that umbilical and middle cerebral artery PI and CPR may be the most important Doppler parameters to watch-out for in monitoring women with PE.